Identifikasi Kebutuhan Pembelajaran Praktik Servis Sepeda Motor dengan Konsep Teaching Factory - Nurcholish Arifin Handoyono; Sigit Purnomo (WACANA AKADEMIKA: Majalah Ilmiah Kependidikan, 2020)
The research aims to identify the learning needs of motorcycle service practice practices with the concept of teaching factory in the PVTM Study Program Universitas Sarjanawiyata Tamansiswa. This type of research is descriptive quantitative. The subject of the study was the head of the PVTM laboratory. The object of the study was the need to learn motorcycle service practice. Data collection by observation, interview, and documentation. Data were analyzed by means of quantitative descriptive. The results showed that: (1) Analysis of the learning needs of motorcycle service practice practices with the concept of teaching factory consists of three processes, namely preparation, learning, and evaluation; and (2) Overview of equipment owned by the PVTM Motorcycle Workshop Production Unit as many as 16 equipment (48.48%) are used classically, while 17 equipment (51.52%) are used in groups. From the equipment, there are 7 equipment (21.21%) categorized as very good, 7 equipment (21.21%) categorized as good, 4 equipment (2.12%) categorized as enough, 13 equipment (39.40%) categorized as less, and 2 equipment (6.06%) categorized as very less. Overall, a percentage of 80.30% is categorized as good.